Atividade antioxidante e antifúngica de óleos essenciais frente a Alternaria alternata - Francio, Iara Emanoely (2020)
Tomatoes are of great importance in the world economy, being host to many pathogens, among them Alternaria alternata, which causes black spot and lesions on vegetables. The use of essential oils has been applied as an alternative control over diseases caused by phytopathogens, this because they have proven antifungal properties. In this context, the objective of this study is to test the activities of essential oils of the cidrozinho-do-campo (Aloysia gratíssima) plant (Salvia microphylla HBK) basil (Ocimum basilicum L.) myrrh (Tetradenia riparia) and thyme (Thymus vulgarisL. ) as antifungal agents against Alternaria alternata strains, in vitro analysis, followed by their in vivo application and their antioxidant action. The oils were obtained by hydrodistillation and chromatography by an external partner. The fungal line was confirmed with DNA extraction and after counting spores in a Neubauer chamber. The antifungal activity of the oils was performed by tests to determine the minimum inhibitory concentration (MIC). Then, the antioxidant activities of the various compounds of interest in the research were determined by the capture methods of the 2,2´-azinobis radical (3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and Iron Reducing Antioxidant Power (FRAP). Finally, the control of A. alternata in tomato was carried out with the use of essential oils in vivo. As initial results, the major compounds of the essential oils were obtained, being β-karyophylene in the oil of Salvia microphylla, geranial in the oil of Ocimum basilicum L., 14-hydroxy-humulene in the oil Tetradenia riparia, thymol in the oil of Thymus vulgaris L. and eucalyptol in the oil of Aloysia gratíssima. 9% growth of the fungus, following O. basilicum L and T. vulgaris L. 59.8% and 58.8%, respectively, which had good effects on the fungi when compared to the control (without treatment). realization of antifungal activity by determining the minimum inhibitory concentration (MIC) the oil of Ocimum basilicum L. and Thymus vulgaris L. inhibited the microorganism at low dosages 3.125 to 6.250 µl / mL respectively, and three at higher inhibitory concentrations 12.5 µl / mL and 25 µl / mL, Tetradenia riparia, Aloysia gratíssima and Salvia microphylla, all of which are considered to have a great potential for inhibition. The antioxidant activity in the FRAP method obtained an average radical scavenging of 66.49 µM of ferrous sufate / g, highlighting the oils of S. microphylla 102.53 µM of ferrous sufate / g and T. vulgaris L. 102, 15 µM of ferrous sufate / g, with an effective activity. Using the ABTS method, we obtained an average radical scavenging of 12, 54 µM trolox / g, highlighting the oilsof O. basilicum L. 15.11 µM trolox / g and Tetradenia riparia 15, 35 µM trolox / g. Finally, the in vivo antifungal action of essential oils obtained T. riparia with greater efficiency in reducing the severity of 66.2%, followed by O. basilicum L and S. microphylla with 54.3% and 50.8%, respectively, which achieved a similar effect in the control of the disease, completing with A. gratíssima and T. vulgaris L, with a reduction of 45.4% and 32.9% respectively, which are intermediate controls, but also promising. The results of this work indicate that the essential oils studied represent an attractive alternative in controlling the growth of A. alternata and of promising potential in the line of alternative products for tomato culture.